Crítica da razão antiutópica: inovação institucional na aurora do Estado moderno - Philippe Oliveira de Almeida (2016)
The liberal doctrine is congenitally refractory to utopianism. For this reason, the western left as proved reticent when the subject is to idealize models of social organization differents from that established by speculative capitalism. However, criticism and utopia represent complementary strengths. Few fields of the humanities are so loaded with anti-utopianism as the legal knowledge. Thus, in order to construct a critical legal thinking, we need to correlate utopianism and Philosophy of Law. In an effort to criticize the prevailing legal order, the vast collection of utopian novel compounds in the West since the sixteenth century can serve as a source of inspiration, emphasizing - against the pensée unique, the naturalization of the status quo - the possibility of alternatives. We are especially interested in delineating a dialogue between the Critical Legal Studies (north american movement that emerged in the 1970s) and the utopian literature. We will specifically investigate the utopias of the sixteenth century, because we believe that returning to the time of emergence of the genre we will be able to prove the indispensability of the link between criticism of society and utopian representation.